Pesantren dan Multikulturalisme di Madura: Adaptasi Nilai Multikultural dalam Menciptakan Kerukunan Masyarakat Multi Etnis dan Agama - Mo’tasim, Mo’tasim; Bakri, Maskuri; Mistar, Junaidi; Ghony, Djunaidi; Purnamasari, Nia Indah (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
The harmony of multi-ethnic and religious communities in an area is always interesting to discuss because it can provide solutions to conflict-affected areas. This phenomenological study aims to analyze the adaptation process of multicultural values carried out by Pesantren Miftahul Qulub in building social harmony in multi-ethnic and religious village of Polagan, Pamekasan, Madura. This phenomenological research demonstrates that multicultural adaptation goes through local culture, moderate school of thoughts, outreach, and social capital. Some of these approaches are the actualization and dissemination of Islamic values and Nahdhatul Ulama (NU) spirit that makes pesantren so easily accepted and mingles within multicultural communities. Seen from a pedagogical perspective, Pesantren Miftahul Qulub emphasizes the community-based learning process. Therefore, this concept can be a reflection for other pesantren, that the curriculum and academic culture must be adapted to the needs of a diverse, dynamic and developing society.